Genome Insight and Comparative Pathogenomic Analysis of Nesterenkonia jeotgali Strain CD08_7 Isolated from Duodenal Mucosa of Celiac Disease Patient - Chander, Atul M.; Nair, Ramesan G.; Kaur, Gurwinder; Kochhar, Rakesh; Dhawan, Devinder K.; Bhadada, Sanjay K.; Mayilraj, Shanmugam (Frontiers in Microbiology, 2017)
Species of the genus Nesterenkonia have been isolated from different ecological niches, especially from saline habitats and reported as weak human pathogens causing asymptomatic bacteraemia. Here, for the first time we are reporting the genome sequence and pathogenomic analysis of a strain designated as CD08_7 isolated from the duodenal mucosa of a celiac disease (CD) patient, identified as Nesterenkonia jeotgali. To date, only five strains of the genus Nesterenkonia (Nesterenkonia massiliensis strain NP1T, Nesterenkonia sp. strain JCM 19054, Nesterenkonia sp. strain F and Nesterenkonia sp. strain AN1) have been whole genome sequenced and annotated. In the present study we have mapped and compared the virulence profile of N. jeotgali strain CD08_7 along with other reference genomes which showed some characteristic features that could contribute to pathogenicity. The RAST (Rapid Annotation using Subsystem Technology) based genome mining revealed more genes responsible for pathogenicity in strain CD08_7 when compared with the other four sequenced strains. The studied categories were resistance to antibiotic and toxic compounds, invasion and intracellular resistance, membrane transport, stress response, osmotic stress, oxidative stress, phages and prophages and iron acquisition. A total of 1431 protein-encoding genes were identified in the genome of strain CD08_7 among which 163 were predicted to contribute for pathogenicity. Out of 163 genes only 59 were common to other genome, which shows the higher levels of genetic richness in strain CD08_7 that may contribute to its functional versatility. This study provides a comprehensive analysis on genome of Nesterenkonia jeotgali strain CD08_7 and possibly indicates its importance as a clinical pathogen.